Different Anti-Contractile Function and Nitric Oxide Production of Thoracic and Abdominal Perivascular Adipose Tissues - Victorio, Jamaira A.; Fontes, Milene T.; Rossoni, Luciana V.; Davel, Ana P. (Frontiers in Physiology, 2016)
Divergent phenotypes between the perivascular adipose tissue (PVAT) surrounding the abdominal and the thoracic aorta might be implicated in regional aortic differences, such as susceptibility to atherosclerosis. Although PVAT of the thoracic aorta exhibits anti-contractile function, the role of PVAT in the regulation of the vascular tone of the abdominal aorta is not well defined. In the present study, we compared the anti-contractile function, nitric oxide (NO) availability, and reactive oxygen species (ROS) formation in PVAT and vessel walls of abdominal and thoracic aorta. Abdominal and thoracic aortic tissue from male Wistar rats were used to perform functional and molecular experiments. PVAT reduced the contraction evoked by phenylephrine in the absence and presence of endothelium in the thoracic aorta, whereas this anti-contractile effect was not observed in the abdominal aorta. Abdominal PVAT exhibited a reduction in endothelial NO synthase (eNOS) expression compared with thoracic PVAT, without differences in eNOS expression in the vessel walls. In agreement with this result, NO production evaluated in situ using 4,5-diaminofluorescein was less pronounced in abdominal compared with thoracic aortic PVAT, whereas no significant difference was observed for endothelial NO production. Moreover, NOS inhibition with L-NAME enhanced the phenylephrine-induced contraction in endothelial-denuded rings with PVAT from thoracic but not abdominal aorta. ROS formation and lipid peroxidation products evaluated through the quantification of hydroethidine fluorescence and 4-hydroxynonenal adducts, respectively, were similar between PVAT and vessel walls from the abdominal and thoracic aorta. Extracellular superoxide dismutase (SOD) expression was similar between the vessel walls and PVAT of the abdominal and thoracic aorta. However, Mn-SOD levels were reduced, while CuZn-SOD levels were increased in abdominal PVAT compared with thoracic aortic PVAT. In conclusion, our results demonstrate that the anti-contractile function of PVAT is lost in the abdominal portion of the aorta through a reduction in eNOS-derived NO production compared with the thoracic aorta. Although relative SOD isoforms are different along the aorta, ROS formation and lipid peroxidation seem to be similar. These findings highlight the specific regional roles of PVAT depots in the control of vascular function that can drive differences in susceptibility to vascular injury.